Implementasi Bantuan Program Peningkatan Kebiasaan Menuju Masyarakat Sejahtera Di Kelambir Lima - Fitra Arlina Nasution (Jurnal Masyarakat Indonesia (Jumas), 2024)
This community service initiative is driven by the goal of improving the well-being of beneficiary families (KPM) from the Family Hope Program (PKH) so that the community can achieve better living standards and welfare. As one of the cities in North Sumatra Province, Kelambir Lima was chosen as the location for this service. The focus of this initiative is to determine whether changes in service practices have an impact on the Family Hope Program (PKH) and community welfare. The aim of this research is to assess the influence of PKH on community welfare. The study involved a sample of 227 KPM, with data collected through questionnaires and analyzed using SEM (Structural Equation Modeling) with Amos software. The hypothesis testing results indicated that the variables of social services, social assistance, and housing have a significant impact on PKH. Additionally, the housing variable has a significant impact on community welfare, while the social services and social assistance variables do not significantly affect community welfare. Furthermore, community welfare does not have a significant impact on the PKH program.